Degradation of phenolic compounds with simultaneous bioelectricity generation in microbial fuel cells: Influence of the dynamic shift in anode microbial community. (November 2019) - Li, Biao; Liu, Xiao-Na; Tang, Chen; Zhou, Jun; Wu, Xia-Yuan; Xie, Xin-Xin; Wei, Ping; Jia, Hong-Hua; Yong, Xiao-Yu
Highlights: Phenolic compounds can be completely degraded and mineralized via ring-cleavage pathway. Voltage generation was inhibited but degradation rate was enhanced under 3.0 g/L phenolic compounds. AMC collaboration enhanced the degradation rate of parent compounds and their intermediates. The fermentative bacteria were prevailed, but electrogenic bacteria were inhibited after the operation. Abstract: This study evaluated the feasibility of microbial fuel cells (MFCs) for simultaneous electricity generation and degradation of phenolic compounds. The voltage generation was inhibited by 36.18–63.90%, but the degradation rate increased by 146.15–392.31% when the initial concentration of syringic acid (SA), vanillic acid (VA), and 4-hydroxybenzoic acid (HBA) increased from 0.3 to 3.0 g/L. The collaboration among the functional microbes significantly enhanced the degradation rate of parent compounds and their intermediates in MFCs systems, while the accumulated intermediates severely inhibited their complete mineralization in fermentative systems. High-throughput sequencing showed that the growth of fermentative bacteria prevailed, but electrogenic bacteria were inhibited in the anode microbial community (AMC) under high concentrations of phenolic compounds (3.0 g/L). These findings provide a better understanding of the dynamic shift and synergy effects of the AMC to evaluate its potential for the treatment of phenolic-containing wastewater.